ANALISIS RASIO PROFITABILITAS DAN RASIO AKTIVITAS MENJADI DASAR PENILAIAN KINERJA KEUANGAN KSP MANDIRI SEJAHTERA - Sitepu, Andres Putranta (EKONOMIKA, 2023)
The purpose of this study is to evaluate the financial performance of KSP Mandiri Sejahtera from 2019 to 2021, specifically focusing on profitability ratios, activity ratios, and comparing their performance with industry benchmarks. The research method used is qualitative, using the financial reports of KSP Mandiri Sejahtera as the main analysis. Secondary data is used, and data collection techniques include interviews and literature study. The results show that KSP Mandiri Sejahtera has performed very well in terms of gross profit margin, exceeding the industry average by an average of 65%. Additionally, net profit margins are also impressive, exceeding the industry average of 34%. Return on investment is considered satisfactory, meeting industry standards at an average of 28%. However, when looking at the activity ratio, KSP Mandiri Sejahtera does not manage its assets effectively. Average accounts receivable turnover was significantly lower than the industry standard at only 5 times, and inventory turnover fell below industry expectations at 1 time. On the other hand, total asset turnover is considered adequate, in line with the industry standard of 1x on average. In conclusion, profitability ratios and activity ratios provide valuable insights into a company's financial performance, resource utilization, cost control measures, and sales effectiveness and efficiency